Corrupção: estudo sobre as formas de mensuração, seus determinantes e perspectivas sobre as formas de combate - Lopes, Marcos Felipe Mendes (2011)
The essential goal of this doctoral thesis is to gather in one piece of work a perspective on the developments of the corruption-related literature. By addressing measurement issues and the impacts of institutional characteristics and training programs on corruption incidence, I intend to present a clear picture on corruption that affects the Brazilian public administration. Results obtained herein allow me to conjecture on some issues. First, measuring corruption is indispensable, so public policies can be more effectively designed in a way they are less subject to corruption incidence. Secondly, there is a need to seek associations between the characteristics of public policy design, municipal characteristics and corruption incidence. Even if clear causal relations are not fully understood, any degree of association between those can assist public agents in performing its functions with less susceptibility to the occurrence of corruption-related frauds. Finally, I pinpoint the manifest relationship between training public agents and corruption incidence: according to the results here obtained, capacitating public agents produces positive effects on public management, with direct impact on the number of findings associated with corruption. As an ideal result, I hope to encourage further research on the topic, hopefully contributing towards a more responsive and effective public management in Brazil.